Application for predicting breast cancer through Google Prediction API. - Silva, Andrio Rodrigo Corrêa da (Anais da Escola Regional de Computação Aplicada à Saúde (ERCAS); 2018: Anais da VI Escola Regional de Computação aplicada à Saúde, 2018)
Breast cancer is a disease that has been affecting thousands of women around the world. Detection of this disease in the initial stage is very important, since a treatment is initiated thus increasing the survival rate. In this paper we discuss the elaboration of an application using a machine learning model trained using the Google Prediction API. This application is able to predict if the tumor of a given patient is classified as benign or malignant.